Internationalization of professional engineers: A challenge for engineering educators - Lloyd, Natalie; Matemba, E. (2014)
Globalisation has forced higher education towards internationalisation and harmonisation in engineering education (Altbach & Knight, 2007). Increased pressure is applied to institutions to demonstrate effectiveness of their engineering programs to produce engineers with competencies enabling them to engage proactively in the global industry (Mhilu, Ilemobade & Olubambi, 2008). Whilst accreditation has been used as method of international mutual-recognition, is accreditation the best method of demonstrating effectiveness? Research shows that international accreditation systems have their short falls, especially in demonstration of global skills, and indicates how the skills can be developed in engineering education (Allan & Chisholm, 2009; Patil & Codner, 2007). Industry perspective research has demonstrated the importance of global skills in engineers and proposed improvement in the engineering education (Zaharim et al, 2009). However the proposed improvements have not taken into consideration their applicability globally. How then do institutions develop appropriate courses of study to equip graduate engineers for the global market? This paper presents current research into a systematic comparative procedure for developing a curriculum that will be globally appropriate.